The Presence, Nature, Cause, and Result of Jesus’s Anger in Mark 1:40–45 - Bruehler, Bart B. (Harvard theological review, 2025)
After a defense of the reading that Jesus was "angry" in Mark 1:41, this investigation explores the nature of anger in light of ancient and contemporary conceptions of emotion, what causes Jesus’s anger in the context, and what results from Jesus’s anger in the story. Jesus’s anger is aroused because the ("leprous") man’s public request for an amazing act of cleansing comes right on the heels of Jesus’s attempt to avoid notoriety about his deeds of power and preach the kingdom more broadly (1:38). Jesus mercifully cleanses the man but then cleverly issues a strict command that the man leave the region, go to Jerusalem, and spend several days there (1:43-44). However, the man and Jesus do not share enough context for him to grasp Jesus’s anger, and so he goes out and proclaims the deed, resulting in what initially troubled Jesus—he can now no longer enter towns to preach (1:45).